Empathic Engagement and Aesthetic Appreciation Between Readers’ Ethnicity and Narratives’ Literary Prestige (Journal of the Digital Humanities Association of Southern Africa, 2024)
Scholars of postcolonial studies have highlighted the role played by identity features in both the production and the reception of literary works. In this paper, we apply computational methods to a corpus of reviews of South-African post-colonial novels, downloaded from the Goodreads platform, in order to assess the influence of sociocultural and intersectional factors on the level of appreciation and identification potential of narratives. In particular, we investigate the effect, on the one hand, of the reader’s ethnicity and, on the other, of the work’s literary prestige on the appreciation and the empathic transportation elicited by narratives in the reader. To operationalize our hypotheses, we collected information on the reviewers’ country of provenance (self-declared by Goodreads users) and on the book’s critical appreciation (via either the award of or the nomination for a literary prize). Such information was compared with: (a) Goodreads star rating scores, indicative of success in the online reading community; (b) usage of empathy lexicon (identified via the Linguistic Inquiry and Word Count tool – in short LIWC), indicative of the reader’s identification in the narrative. Results indicate that readers typically empathize more with works that reflect themes from their own country and tend to award them with slightly higher ratings. Furthermore, we found that critically appreciated books, though collecting higher ratings, elicit a smaller empathic response in the reader than those that did not win or were not nominated for any literary prize.
Keywords: Book reviews; South Africa; Post-Colonialism; Empathy; Literary Prestige